INOR ESTABLISHES COLLABORATION TO DEVELOP FUTURE TECHNOLOGY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 22 August 2015 – The Institute of Nano Optoelectronics Research and Technology (INOR) which was established since January 1, 2015 has been involved in many collaborations with various parties in advancing the research on optoelectronics to develop technologies for the future.